(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
this paper a fuzzy reliability of a different types of a systems is calculated by using a reduction method to series system and applying Intuitionistic rules of fuzzy Sets which deals with uncertainty and incomplete informations to calculate the fuzzy reliability via illustrative example is presented with conclusions.